Assessing disease risk perceptions of wild meat in savanna borderland settlements in Kenya and Tanzania - Patel, Ekta H.; Martin, Andimile; Funk, Stephan M.; Yongo, Moses; Floros, Camilla; Thomson, Julie; Fa, Julia E. (Frontiers in Ecology and Evolution, 2023)
Wild meat hunting and trade across African savannas is widespread. We interviewed 299 people in rural settlements along the Kenya-Tanzania border to examine impacts of COVID-19 on wild meat consumption and perceptions about wild meat activities associated with zoonotic disease risks. Education level played a key part in understanding COVID-19 transmission. Information about the pandemic was mostly acquired from the media. Nearly all respondents recognized that COVID-19 originated in China. As many as 70% reported no impact of COVID-19 on wild meat consumption; some believed that there was an increase. Over half of the respondents believed that consumption of wild meat leads to food-borne illnesses. Respondents recognized disease risks such as anthrax and brucellosis and accepted that people slaughtering and handling wild meat with open cuts were at greater risk. Ungulates were the most consumed animals, followed by birds, rodents, and shrews. Respondents perceived that hyenas, monkeys, donkeys, and snakes were riskier to eat. More than 90% of the respondents understood that handwashing with soap reduces risks. Country level (11 answers), education and gender (three answers each) and household economy (158 answers) were significant. Country differences were linked to differences in nature legislation; 50% of Kenyan respondents believed that wild meat should not be sold because of conservation concerns. Men were more worried about getting COVID-19 from live animals and perceived that wildlife should not be sold because of conservation reasons. Overall, there was a very strong inclination to stop buying wild meat if other meats were less expensive. Our results allow us to better understand the impact of the COVID-19 pandemic on wild meat-related activities. Differences between countries can frame the attitudes to wild meat since wild meat trade and consumption were found to be country specific.